Period-oriented spatial comparative evaluation of biodiversity conservation effectiveness in China - Chen, Ziqi; Liu, Zhaoli; Hou, Guanglei; Dong, Kaikai; Zhang, Yanhong; Yang, Changbao (Frontiers in Ecology and Evolution, 2022)
The period-oriented comparative evaluation of biodiversity conservation effectiveness is the main basis for implementing the transfer payment policy of ecological compensation. In response to the lack of such a spatial comparative assessment system, the paper proposes a method to construct the Period Conservation Effectiveness Index (PCEI) and applies it to the spatial comparative assessment of Chinese biodiversity conservation effectiveness in three periods from 1990 to 2015, while validating the rationality of the reference. The results show that (1) spatially, the biodiversity conservation effectiveness of key ecological function areas(KEFAs) in Central China and South China is better, while Southwest and Northwest are in the middle, and East China and Northeast are worse; (2) temporally, the biodiversity conservation effectiveness of KEFAs as a whole is worse from 1990 to 2000, best from 2000 to 2010, and middle from 2010 to 2015; (3) The existing reference establishment methods can reflect the spatial differences of natural environment background, which effectively support the spatial comparison assessment of biodiversity conservation effectiveness. This study constructs a spatial comparison assessment system of biodiversity conservation effectiveness within periods, which can provide a scientific basis for national and even global large-scale ecological compensation and other fund allocation methods.